Polyethyleneimine coated Fe3O4 magnetic nanoparticles induce autophagy, NF-κB and TGF-β signaling pathway activation in HeLa cervical carcinoma cells via reactive oxygen species generation. (30th October 2019) - Man, Shuli; Li, Miao; Zhou, Jin; Wang, Haiyue; Zhang, Jinyan; Ma, Long
Abstract : Fe3 O4 magnetic nanoparticles (MNPs) are proved to induce autophagy, NF-κB and TGF-β signaling pathways activation in cancer cells, which is switched on by induced ROS. Abstract : Fe3 O4 magnetic nanoparticles (MNPs), as one of the most intensively researched NPs, have a range of applications in cancer treatments. In current research, we have focused on the influences of MNPs on cancer cells. We chose polyethyleneimine (PEI) coated MNPs (PEI-MNPs) as a model and they are colloidally stable in biological media. It can be proved that PEI-MNPs result in autophagy induction via mTOR-Akt-p70S6 K and ATG7 signaling pathways. For the first time, we have reported that PEI-MNPs activate both NF-κB and TGF-β signaling, two key pro-inflammatory pathways, in cancer cells. More significantly, we have found that autophagy induction and NF-κB and TGF-β activation can be efficiently suppressed through the inhibition of PEI-MNP dependent reactive oxygen species (ROS) over-production. ROS are deemed as a 'double edge sword' for cancer cells, owing to the cancer-suppressing and cancer-promoting actions. Our findings would be useful for designing MNPs induced ROS anti-cancer strategies or diminishing long-term toxic effects.